PENERAPAN MODEL PEMBELAJARAN TGT UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV MATERI SIKLUS HIDUP HEWAN SDN SUMUR WELUT I SURABAYA - ARDIANSA, JOFI; , JULIANTO (Jurnal Penelitian Pendidikan Guru Sekolah Dasar, 2018)
Abstract The purpose of this research is to describe student learning outcomes by apply the TGT learning model. This research uses Classroom Action Research method using data collection technique by observation and test. Teacher activity has increased two cycles. In cycle I the average achievement of 74,4, while in cycle II the average achievement of 86,85. Student activity has increased for two cycles. In cycle I the average achievement of 73,15, while in cycle II the average achievementof 86.45. The increase also occurred in student learning outcomes, in the first cycle , students classical completeness 61.53% with an average of 72.6, while in cycle II classical completeness reached 84.61% with an average of 82.5. It can be concluded that the application of the TGT learning model can improve the learning outcomes of fourth grade students of Sumur Welut Elementary School 1 Surabaya. Keywords: Model, TGT, and Learning Outcomes